The completed SDSS-IV extended Baryon Oscillation Spectroscopic Survey: large-scale structure catalogues and measurement of the isotropic BAO between redshift 0.6 and 1.1 for the Emission Line Galaxy Sample. Issue 3 (28th October 2020) - Raichoor, Anand; de Mattia, Arnaud; Ross, Ashley J; Zhao, Cheng; Alam, Shadab; Avila, Santiago; Bautista, Julian; Brinkmann, Jonathan; Brownstein, Joel R; Burtin, Etienne; Chapman, Michael J; Chuang, Chia-Hsun; et al.
ABSTRACT: We present the Emission Line Galaxy (ELG) sample of the extended Baryon Oscillation Spectroscopic Survey from the Sloan Digital Sky Survey IV Data Release 16. We describe the observations and redshift measurement for the 269 243 observed ELG spectra, and then present the large-scale structure catalogues, used for the cosmological analysis, and made of 173 736 reliable spectroscopic redshifts between 0.6 and 1.1. We perform a spherically averaged baryon acoustic oscillations (BAO) measurement in configuration space, with density field reconstruction: the data two-point correlation function shows a feature consistent with that of the BAO, the BAO model being only weakly preferred over a model without BAO (Δχ 2 < 1). Fitting a model constrained to have a BAO feature provides a 3.2 per cent measurement of the spherically averaged BAO distance D V ( z eff )/ r drag = 18.23 ± 0.58 at the effective redshift z eff = 0.845.